2005
DOI: 10.1073/pnas.0509541102
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeting of dendritic cells for activation of cellular immunity using vaccine carriers based on pH-responsive microparticles

Abstract: Activating the immune system to trigger a specific response is a major challenge in vaccine development. In particular, activating sufficient cytotoxic T lymphocyte-mediated cellular immunity, which is crucial for the treatment of many diseases including cancer and AIDS, has proven to be especially challenging. In this study, antigens were encapsulated in acid-degradable polymeric particle carriers to cascade cytotoxic T lymphocyte activation. To target dendritic cells, the most potent antigen-presenting cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
139
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 22 publications
1
139
0
3
Order By: Relevance
“…With regard to recognition, some subclasses of dendritic cell possess an endocytic receptor, DEC205 (ref. 20), which has been successfully used to enhance dendritic-cell uptake, for example with an antigen or a biomaterial particle conjugated to anti-DEC205 antibodies 21,22 . Recruitment involves chemoattracting other APCs to the delivery site, and strategies include the use, variously, Complement-activating, nucleophile-containing polymeric nanoparticles 28 Induced antigen-specific monoclonal antibody; induced IFN-γ-producing antigenspecific CD8 + T cells 28 Recombinant C3d 72,95 Recombinant, trimeric C3d protein conjugated to protein antigen through an avidin bridge 18 Induced a more robust and protective response to antigen when administered with IFA than when protein antigen administered in IFA or with alum 18 Recombinant, trimeric C3d-antigen fusion DNA vaccine 95 Generated higher-binding, early-appearing and neutralizing antibody responses; increased the number of IFN-γ-producing antigen-specific CD8 + T cells 95 The responses shown are related to engineering approaches to triggering these pathways or types of immunity using biomaterials.…”
Section: Materials For Enhancing Antigen Uptake By Apcsmentioning
confidence: 99%
“…With regard to recognition, some subclasses of dendritic cell possess an endocytic receptor, DEC205 (ref. 20), which has been successfully used to enhance dendritic-cell uptake, for example with an antigen or a biomaterial particle conjugated to anti-DEC205 antibodies 21,22 . Recruitment involves chemoattracting other APCs to the delivery site, and strategies include the use, variously, Complement-activating, nucleophile-containing polymeric nanoparticles 28 Induced antigen-specific monoclonal antibody; induced IFN-γ-producing antigenspecific CD8 + T cells 28 Recombinant C3d 72,95 Recombinant, trimeric C3d protein conjugated to protein antigen through an avidin bridge 18 Induced a more robust and protective response to antigen when administered with IFA than when protein antigen administered in IFA or with alum 18 Recombinant, trimeric C3d-antigen fusion DNA vaccine 95 Generated higher-binding, early-appearing and neutralizing antibody responses; increased the number of IFN-γ-producing antigen-specific CD8 + T cells 95 The responses shown are related to engineering approaches to triggering these pathways or types of immunity using biomaterials.…”
Section: Materials For Enhancing Antigen Uptake By Apcsmentioning
confidence: 99%
“…Antigen targeting [1][2][3][4][5] and adjuvancy schemes 6,7 that respectively facilitate delivery of antigen to dendritic cells and elicit their activation have been explored in vaccine development. Here we investigate whether nanoparticles can be used as a vaccine platform by targeting lymph noderesiding dendritic cells via interstitial flow and activating these cells by in situ complement activation.…”
mentioning
confidence: 99%
“…Strategies for antigen delivery have recently focused on in vivo targeting of dendritic cells through the use of monoclonal antibodies either fused with protein 1,2,4 or grafted to the surface of microparticles 3 . Such strategies often target peripheral dendritic cells in skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kwon et al conjugated anti-DEC205 on microparticles and showed that these particles are taken up by DCs three times higher than non-targeted counterparts in vivo. 44 It has been shown that human and murine DCs and macrophages express mannose receptor (MR) on their surface. Several studies have confirmed the feasibility of using mannose or mannan to target protein antigens, liposomes, and other micro and NPs to APCs.…”
Section: Targeted Delivery To Peripheral Dcsmentioning
confidence: 99%